Biomarkers of 4-hydroxy-N, N-methylpropyltryptamine (4-OH-MPT) intake identified from human hepatocyte incubations. (2nd December 2022) - Carlier, Jeremy; Malaca, Sara; Huestis, Marilyn A.; Tagliabracci, Adriano; Tini, Anastasio; Busardò, Francesco P.
ABSTRACT: Background: 4-Hydroxy- N, N -methylpropyltryptamine (4-OH-MPT) is a psychedelic tryptamine whose use is regulated in several countries. Due to unspecific effects, consumption can be ascertained only through toxicological analyses. However, the trace amounts of tryptamines are usually challenging to detect in biological samples. 4-OH-MPT metabolism was characterized to identify optimal metabolite markers of intake in clinical/forensic toxicology. Research design and methods: 4-OH-MPT was incubated with 10-donor-pooled human hepatocytes to simulate in vivo conditions; samples were analyzed by liquid chromatography-high-resolution tandem mass spectrometry (LC-HRMS/MS), and data were processed with Compound Discoverer from Thermo Scientific. LC-HRMS/MS and data mining were supported by in silico metabolite predictions (GLORYx). Results: Three phase I and four phase II metabolites were identified, including N -oxidation and N -demethylation at the alkylamine chain, and O -glucuronidation and sulfation at the hydroxylindole core. Conclusions: 4-OH-MPT metabolic fate was consistent with the human metabolism of tryptamine analogues: we suggest 4-OH-MPT- N -oxide and 4-hydroxy- N, N -propyltryptamine (4-OH-PT) as metabolite biomarkers of 4-OH-MPT consumption after glucuronide/sulfate hydrolysis in biological samples to improve detection of 4-OH-MPT and phase I metabolites; 4-OH-MPT-glucuronide is suggested as an additional biomarker when hydrolysis is not performed. Further research on the metabolism of structural analogues is necessary to evaluate the specificity of 4-OH-MPT metabolite biomarkers.